The Influence of Product Differentiation, Price and Positioning on Purchasing Decisions at Niceso Stores in South Tangerang - Monika Claudia Sarita; Mohamad Trio Febriyantoro; Zulkifli Zulkifli; Dede Suleman; Fendi Saputra; Yohanes Totok Suyoto (Priviet Social Sciences Journal, 2022)
This study aims to analyze the effect of product differentiation, price and positioning on purchasing decisions. This type of research uses quantitative, the population used is Nice so product customers with a sample taken of 122 respondents. The method used is multiple linear regression analysis with processing using SPSS 26 software. The sampling technique in this study used a purposive sampling technique. The results of the study show that product differentiation, price and positioning have a positive and significant effect on purchasing decisions